Walk Through the Door: Storying the Experiences of Older Adults Living in Supportive Shelter Through Research-Based Theatre - Herrera, Ana C.; Walsh, Christine A.; Grittner, Alison (Art/Research International, 2026)
Traditional forms of research highlight the informational content of data collection, largely disregarding affective and embodied aspects of participants’ experiences. Incorporating research-based theatre (RbT) into an inquiry process can bring participants’ voices to the forefront and may thereby enrich the study findings. By integrating a theatrical approach for observation, analysis, and knowledge dissemination, RbT can illuminate dramatic aspects of participants’ testimonies, providing key insights into addressing complex social issues. A theatrical analysis of the Aging in the Right Place (AIRP) research project data were used to explore participants’ affective experiences. The AIRP study elicited the perspectives of 35 older adults, age 55+, on the socio-spatial needs for aging in place in four temporary supportive shelters in Calgary, Alberta. This article discusses the process and findings of writing a theatrical piece drawing upon qualitative in-depth interviews and photovoice methods, aiming to more fully understand the socio-emotional aspects of older adults living in temporary supportive shelters.